Recognition of the Concept of Urban Identity through the Place Attachment Case Study: Konya, Alaaddin Hill - Khaleghimoghaddam, Navid; Yılmaz Çakmak, Bilgehan (ICONARCH International Congress of Architecture and Planning, 2017)
The “place attachment” is a definition by the meeting point of activities, functional elements, and abstract meanings of the place. A place can come to the scene by the place attachment which has emotional and behavioral characteristics for people. Squares, plays an important role in conceptual, functional and physical aspects at the point of increasing the quality of urban spaces. In this context, it is an important issue to consider the impressive factors that connect people to the space and the square, in the case that the squares are desired, preferred and identity-possessed. This research examines the concept of place attachment through the process of environmental psychology, explains the factors of feeling belonging to the place, and examines the role of place in the formation of the desired and identifiable urban squares. It is based on a cognitive approach aimed at evaluating space perception on Alaaddin Hill in Konya city. This research and field study was carried out by observation and questionnaire on square users, and as well as by analyzing descriptive and inferential statistics. The findings of the study show that most of the users have place attachment. Thus, the user's perception and mind, proves that this square has an impressive role in gaining identity. The article thus prove that there is a relationship between place attachment and space identity, which can be addressed in the design of urban squares. Alaaddin Mosque from the Seljuk period is at the center of this square and is considered as an important factor in the user's place attachment. The easy and convenient access to the meadow enhances, the presence of trees, plants and landscapes, cafes, walking routes, located in the square of the city center and appropriate abstract and concrete landscapes increases the feeling of being connected to the place. It is expected that the results of this research will be effective in designing new squares of contemporary cities.